Perception of reality vs. professional reality in unilateral lower limb prothesis user amputees - Rocha, Jackelyn M. (2021)
Introduction: To understand the perception of lower limb amputees, regarding movement with prothesis, wellbeing, and perceived appearance, and to elaborate a socio-professional demographic and clinical study, to establish patterns and relations that may help enjoy a better quality of life. Methods: We conducted a questionnaire survey of socio-professional, demographic, and clinical data of 103 lower limb amputees, between 29th March 2018 and 9th July 2018. Seventy-four interviewees also replied to sub-scales from the PEQPT questionnaire. Results: The values attributed to movement, wellbeing, and perceived appearance, were on average, 59.3%, 62.7%, and 75.3%, respectively. A large number of patients (80.6%) stated that because of the amputation, there is an increase in the monthly expenses and a reduction in the monthly income. The value attributed to the prosthetics perceived appearance for males and females, was, on average, 79.32% and 65.03% respectively, this difference being significant. Conclusions: Our main aim was to study the perception regarding movement with a prothesis; the perception regarding wellbeing with prothesis; the perception regarding prothesis perceived appearance; to elaborate a socio-professional, demographic, and clinical analysis. In the first three points, the values attributed are good, mainly the perceived appearance issue. In the fourth point, we can conclude that it was successfully undertaken.